Shipping As an Instrument of Maritime Diplomacy: A Literature Review of its Influence in Inter-State Relations - David, Muhammad (Pancasila and Civics Education Journal, 2025)
Shipping plays an important role in international relations, not only as a means of transportation, but also as an instrument of maritime diplomacy for cultural exchange, trade, and geopolitical strengthening. As the largest archipelagic country in the world, Indonesia has great potential to utilize shipping to improve regional stability, maritime security, and diplomatic relations. However, challenges such as water security, limited infrastructure, and lack of diplomatic capacity still hinder the optimization of this potential. This study uses a literature review to analyze the role of shipping in maritime diplomacy, both historically and modernly, by taking lessons from countries such as Japan and the UK. The results show that shipping can strengthen bilateral and multilateral relations through trade, maritime security, and cultural promotion. International collaboration through multilateral platforms, such as ASEAN, is important to address issues such as piracy, climate change, and sustainable management of marine resources. Promotion of maritime culture can increase Indonesia's soft power, while the implementation of modern technology in navigation and surveillance can face global challenges. With a comprehensive strategy, Indonesia can optimize its maritime potential to support sustainable regional stability and growth.